2005
DOI: 10.1007/s11194-005-1212-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Relapse Prevention Program on Sexual Recidivism: Final Results From California?s Sex Offender Treatment and Evaluation Project (SOTEP)

Abstract: Final results from a longitudinal investigation of the effectiveness of cognitive-behavioral treatment with sexual offenders are presented. The study was a randomized clinical trial that compared the reoffense rates of offenders treated in an inpatient relapse prevention (RP) program with the rates of offenders in two (untreated) prison control groups. No significant differences were found among the three groups in their rates of sexual or violent reoffending over an 8-year follow-up period. This null result w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…Previous studies have also found that phallometric testing performed prior to participation in sex offender-specific treatment is associated with sexual recidivism, whereas testing after treatment is not (Rice, Quinsey, & Harris, 1991). In contrast, other studies have found that posttreatment assessments are associated with sexual recidivism (Clift, Rajlic, & Gretton, 2009; Jones, 2014; Marques, Wiederanders, Day, Nelson, & van Ommeren, 2005). Samples of sexual offenders against children can also differ between studies in terms of the age and sex of their victims as well as their familial relationship to their victims (e.g., biologically related or unrelated to victims).…”
mentioning
confidence: 83%
“…Previous studies have also found that phallometric testing performed prior to participation in sex offender-specific treatment is associated with sexual recidivism, whereas testing after treatment is not (Rice, Quinsey, & Harris, 1991). In contrast, other studies have found that posttreatment assessments are associated with sexual recidivism (Clift, Rajlic, & Gretton, 2009; Jones, 2014; Marques, Wiederanders, Day, Nelson, & van Ommeren, 2005). Samples of sexual offenders against children can also differ between studies in terms of the age and sex of their victims as well as their familial relationship to their victims (e.g., biologically related or unrelated to victims).…”
mentioning
confidence: 83%
“…This information can be important for decisions about unsupervised privileges and for risk management in general. For example, Marques et al ( 2005 ) reported, that sex offenders treated with the RP approach and who successfully learned coping skills had significantly lower recidivism rates (13.5%) than sex offenders who did not learned coping strategies successful (27.2%). This difference with regards to re-offense rates was more dominant in the group of high-risk sex offenders and most dominant in the group of child molesters.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the first two issues of Annals had several papers on the neurobiology of sexual offending (e.g., Hucker, Langevin, & Bain, 1988), something that the field has picked up again as new brain scanning technologies have become more available (e.g., Cantor et al, 2015). Early issues of the journal included preliminary results from the Sex Offender Treatment Evaluation Project run in California, still the largest and arguably the most important randomized clinical trial evaluating treatment for adults who have sexually offended (Miner, Marques, Day, & Nelson, 1990; the final evaluation results were also published in this journal, by Marques, Wiederanders, Day, Nelson, & Van Ommeren, 2005), and validation studies of phallometric testing for sexual arousal to rape (e.g., Lalumière & Quinsey, 1993; Marshall, Seidman, & Barbaree, 1991). Seminal articles on etiology, assessment, and treatment have been published over the past 30 years: We have come a long way, and there is still much more work to do.…”
mentioning
confidence: 99%